Ecological divergence of wild strawberry DNA methylation patterns at distinct spatial scales - Kort, Hanne de; Panis, Bartholomeus; Deforce, Dieter; Nieuwerburgh, Filip van; Honnay, Ollivier (Wiley, 2020)
Epigenetic change is considered relatively unstable and short‐lived, raising questions of its contribution to long‐term adaptive potential. However, epigenetic modifications can accumulate in the presence of environmental stress, resulting in beneficial epigenetic memories where environments are challenging. Diverging epigenetic memories have been observed across large spatial scales, and can persist through multiple generations. It is unknown, however, to what extent epigenetic variation contributes to fine‐scale population structure and evolution. We compared DNA methylation patterns between a steep, altitudinal gradient (<2 km) and a wide spatial gradient (>500 km) using whole genome bisulphite sequencing data from 30 Fragaria vesca plants germinated and grown in controlled conditions. To assess the stability of spatial epigenetic variation in the presence of an environmental stressor, we applied acute drought stress to part of the plants and quantified drought‐induced changes in DNA methylation signatures. We find that epigenetic memories and genomic islands of epigenetic divergence arise even at fine spatial scale, and that distinct spatial scales are featured by distinct epigenetic patterns. For example, demethylation of transposable elements consistently occurred at the large but not the fine spatial scale, while methylation differentiation for most biological processes were shared between spatial scales. Acute drought stress did not result in significant epigenetic differentiation. Our results indicate that population history, rather than short‐term environmental stress, plays a dominant role in shaping epigenetic signatures. Specifically, repeated historical stress levels associated with heterogeneous environmental conditions may be required for acquiring a stable epigenetic memory and for coping with future environmental change.